Splicing analysis of 26 F8 nucleotide variations using a minigene assay. Issue 2 (28th January 2019) - Jourdy, Yohann; Fretigny, Mathilde; Nougier, Christophe; Négrier, Claude; Bozon, Dominique; Vinciguerra, Christine
Abstract : Background: Classically, the study of splicing impact of variation located near the splice site is performed by both in silico and mRNA analysis. However, RNA sample was rarely available. Objective: To characterize a panel of putative haemophilia A splicing variations. Materials and methods: Twenty‐six F8 variations identified from a cohort of 2075 haemophilia A families were studied using both bioinformatic tools and in vitro minigene assays in HeLa and Huh7 cells. Results: An aberrant splicing was demonstrated for 21/26 tested sequence variations. A good correlation between in silico and in vitro analysis was obtained for variations affecting donor splice site (12/14) and for the synonymous variations located inside an exon (6/6). Conversely, no concordant results were observed for the six variations affecting acceptor splice sites. The variations resulted more frequently in exon skipping (n = 13) than in activation of nearby cryptic splice sites (n = 5), in use of a de novo splice site (n = 2) or in insertion of large intronic sequences (n = 1). This study allowed to reclassify 5 synonymous substitutions c.1167A>G (p.Gln389Gln), c.1569G>T (p.Leu523Leu), c.1752G>A (p.Gln584Gln), c.5586G>A (p.Leu1862Leu) and c.6066C>T (p.Gly2022Gly) as splicing variations. The pathological significance of five variations remained unclear (c.222G>A [p.Thr74Thr], c.237C>T [p.Asn79Asn], c.240C>T [p.Ile80Ile], c.2113+5_2113+8del and c.2113+5G>A). Discussion: The minigene assay herein gave additional evidences for the clinical significance of 21/26 F8 putative splice site mutations. Such investigation should be performed for each F8 putative splice site variation for which no mRNA sample is available, notably to greatly improve the genetic counselling given to female carriers.